Analysis of social network implementation as a tool for determining the structure of crime networks - Aprianus Daniel Lekitonung (Institute of Computer Science (IOCS), 2023)
Social network analysis (SNA) is a process of mapping and analyzing interactions between people in social media, including crime. SNA can be used to determine network structure and relationships between criminal network actors through the social media used. After initial investigation, this study used the hashtag